Bones for Barnum Brown : Adventures of a Dinosaur Hunter - Bird, Roland T. (Roland Thaxter), 1899-1978 (Book collections on Project MUSE., 1985)
Roland Thaxter Bird, universally and affectionately known to friends and associates as R.T., achieved a kind of Horatio Alger success in the scientific world of dinosaur studies. Forced to drop out of school at a young age by ill health, he was a cowboy who traveled from job to job by motorcycle until he met Barnum Brown, Curator of Vertebrae Paleontology at the American Museum of Natural History in New York and a leader in the study of dinosaurs. Beginning in 1934, Bird spent many years as an employee of the museum and as Brown's right-hand man in the field. His chart of the Howe Quarry.